Rapid on-site detection of harmful algal blooms: real-time cyanobacteria identification using Oxford Nanopore sequencing - Potvin, Marianne; Gauthier, Jeff; Langevin, Christophe; Mohit, Vani; da Costa, Naíla Barbosa; Deschênes, Thomas; Pomerleau, Maude; Kukavica-Ibrulj, Irena; Verreault, Daniel; Comte, Jérôme; Levesque, Roger C. (Frontiers in Microbiology, 2023)
With the increasing occurrence and severity of cyanobacterial harmful algal blooms (cHAB) at the global scale, there is an urgent need for rapid, accurate, accessible, and cost-effective detection tools. Here, we detail the RosHAB workflow, an innovative, inthe-field applicable genomics approach for real-time, early detection of cHAB outbreaks.We present how the proposed workflow offers consistent taxonomic identification of water samples in comparison to traditional microscopic analyses in a few hours and discuss how the generated data can be used to deepen our understanding on cyanobacteria ecology and forecast HABs events. In parallel, processed water samples will be used to iteratively build the International cyanobacterial toxin database (ICYATOX; www.icyatox.ca) containing the analysis of novel cyanobacterial genomes, including phenomics and genomics metadata. Ultimately, RosHAB will 1) improve the accuracy of on-site rapid diagnostics, 2) standardize genomic procedures in the field, 3) facilitate these genomics procedures for non-scientific personnel, and 4) identify prognostic markers for evidence-based decisions in HABs surveillance.